Extension of the useful life of reinforced concrete structures exposed to marine environments through the application of electrochemical techniques - Garcés Terradillos, Pedro; Climent, Miguel-Ángel; Carmona, Jesús; Sánchez Rojas, María José (Revista ALCONPAT, 2021)
In this work, the feasibility of a combined treatment of electrochemical chloride extraction (ECE) and cathodic protection (CP) in reinforced concrete structures using a conductive cement-graphite paste as anode has been studied. It has been proven that the prior application of an electrochemical chloride extraction treatment leads to greater durability of the anode. It has been shown that for reinforced concrete structures located in aggressive marine environments, the combination of electrochemical treatments, first ECE to reduce the chloride content and then CP to maintain passivation conditions, is capable of providing adequate protection conditions for the reinforcement, provided that the appropriate current density value is applied, according to the average content of chlorides present in the reinforced concrete structures.